Women's Formal Help-Seeking Before and After Their Abusive Partner Initiates Relationship Violence Treatment. (February 2023) - Murphy, Christopher M.; Nnawulezi, Nkiru; Ting, Laura
Intimate partner violence survivors ( N = 122) reported on formal help-seeking before and after their male partners enrolled in a Relationship Violence Intervention Program (RVIP). At baseline, only 20% of survivors had ever received domestic abuse (DA) counseling. DA counseling was more common among survivors with more extensive partner abuse exposures, and for black women residing in suburban versus urban communities. New help-seeking was associated with survivor perceptions of the abusive partner's stage of change. RVIP impact may be enhanced through culturally sensitive survivor outreach that is responsive to a broad range of needs and includes repeated contact over time.